INTERNALISASI NILAI-NILAI RELIGIUS BERBASIS MULTIKULTURAL DALAM MEMBENTUK KARAKTER TOLERAN DI MA’HAD SALAFIYAH SYAFI’IYAH SUKOREJO SITUBONDO - Fitriyah, Alfina Wildatul (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
The turn of the times raises competitiveness in various aspects of life, the development of education is the main source of interest to put every human being competing how to be able to balance the potential and demands of the times. Multicultural education provides equal learning opportunities to students regardless of their differences. That is, multicultural education is an educational approach that does not differentiate between cultures, ethnicities, religions, and other differences in the sense that all are considered equal, have the same opportunities and opportunities, and can be harmonious without only favoring each group let alone scorn or consider other groups inferior or even enemies to their groups. One of the urgent values that need to be internalized is the value of multicultal religion to form a tolerant person and character that unites affection and psychomotor in facing social life. The research method used is descriptive qualitative method, which is a method carried out by searching for data that can provide a clear picture of the internalization of multicultural-based religious values in shaping tolerant character in ma'had salafiyah syafi'iyah sukorejo situbondo. The cooperation of all parties, both internal and external in the realm of education, partnership and society, has a positive impact on the results of the internalization of multicultural-based religious values in shaping tolerant character in ma'had salafiyah syafi'iyah sukorejo situbondo, So that each graduate is able and ready to face social life in a peaceful, safe and peaceful society.